The discursive construction of HIV stigma in Irish print media. (May 2023) - Vaughan, Elena; Power, Martin
As interlocutors in national level discourse with the power to influence public opinion and inform policy, the news media are an important data source in understanding the constitutive roles played by culture and discourse in shaping health experiences and outcomes. This paper reports on a critical discourse analysis of news media coverage of HIV in the Republic of Ireland between 2006 and 2016. This period is significant because of the considerable increase in new HIV diagnoses that occurred in Ireland after the 2008 recession. Analysis of articles ( n = 103) demonstrated a pattern of dividing practices whereby people living with or affected by HIV were frequently positioned as somatically and morally deficient via discourses of risk and responsibility. Little focus was given over to examination of the structural drivers of HIV, occluding the social context of the epidemic. The findings suggest that media discourses on HIV have the potential to other people living with HIV and generate stigma by invoking a dynamic of blame and shame frequently implicated in the stigma process.